An investigation of resurgence of reinforced behavioral variability in humans. Issue 3 (12th November 2020) - Galizio, Ann; Friedel, Jonathan E.; Odum, Amy L.
Abstract : The present study examined resurgence of reinforced variability in college students, who completed a 3‐phase computer‐based variability task. In the first phase, baseline, points were delivered for drawing rectangles that sufficiently differed from previous rectangles in terms of a target dimension (size or location, counterbalanced) but were sufficiently similar in terms of the alternative dimension. In the second phase, alternative, points were only delivered for rectangles that were sufficiently different in terms of the alternative dimension, but repetitive in terms of the target dimension. In the third phase, extinction, no points were delivered. In baseline, participants made rectangles that were highly varied in terms of the target dimension and less varied in terms of the alternative dimension, and vice versa in the alternative phase. During extinction, levels of variability increased for the target dimension, providing evidence for resurgence of reinforced variability of a specific dimension of behavior. However, levels of variability also remained high for the alternative dimension, indicating that extinction‐induced response variability may also have impacted the results. Although future research is needed to explore other explanations, the results of this study replicate prior research with pigeons and provide some support for the notion of variability as an operant.